2018
DOI: 10.4236/jcdsa.2018.81004
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Microcapsules Containing Camellia Oil with Heterocoagulation between Chitosan and Oleic Acid

Abstract: It was tried to microencapsulate camellia oil using heterocoagulation between fatty acid dissolved in camellia oil and chitosan dissolved in the continuous water phase. Oleic acid as a fatty acid was dissolved in camellia oil in order to certainly form the microcapsule shell made from oleic acid and chitosan. The microcapsules were observed with optical microscope and characterized about the diameters, ζ-potential, FTIR analysis and adhesion feature on human hair.Microcapsules with the mean diameter in the ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Figure 3A shows the microphotograph of the oil droplets in the oil-in-water emulsion, and Figure 3B shows the dehydrated SFN microcapsules resuspended in an aqueous solution. The average diameter of the oil droplets before dehydration was 6.9 ± 2.3 µm, in the same order of magnitude as that reported by Saito et al [30] for Camellia oil emulsion (equal to 3.9 µm). Zhu et al [31] reported a 3.9 µm for Perilla seed and soybean oils emulsion microcapsules, agreeing with the values obtained in the present work.…”
Section: Particle Sizesupporting
confidence: 86%
“…Figure 3A shows the microphotograph of the oil droplets in the oil-in-water emulsion, and Figure 3B shows the dehydrated SFN microcapsules resuspended in an aqueous solution. The average diameter of the oil droplets before dehydration was 6.9 ± 2.3 µm, in the same order of magnitude as that reported by Saito et al [30] for Camellia oil emulsion (equal to 3.9 µm). Zhu et al [31] reported a 3.9 µm for Perilla seed and soybean oils emulsion microcapsules, agreeing with the values obtained in the present work.…”
Section: Particle Sizesupporting
confidence: 86%
“…The obtained core-shell microcapsules were tested as a dressing material to be applied on hair. Their mean diameters ranged from 1.5 μm to 4.5 μm and were adherent on the surface of human hair, being stable both before and after drying [ 208 ]. A microparticulate system based on the zein and keratin proteins was developed for the release of fragrances on hair.…”
Section: Applications Of Micro-/nanoencapsulated Fragrances and Flmentioning
confidence: 99%